The fathers of the church : a comprehensive introduction - Drobner, Hubertus R.; Schatzmann, Siegfried S. (Peabody, Mass. : Hendrickson Publishers, 2007)
"The Fathers of the Church: A Comprehensive Introduction presents the most important authors and works of the early history of Christian literature. Spanning the first seven hundred years of Christianity, Hubertus R. Drobner introduces writers such as Philo, Origen, Eusebius, Jerome, and Augustine, among many others. All of the authors are presented in their respective political, social, ecclesiastical, and cultural contexts, and are organized in terms of bibliographies, editions, English translations, ancillary sources, and relevant literature."--BOOK JACKET.
Introduction: Patrology as a Subject -- Pt. 1. Apostolic and Postapostolic Literature -- Introduction: The Rise of Christian Literature -- Ch. 1. Biblical Apocrypha -- Ch. 2. Postapostolic Literature -- Pt. 2. Literature of the Period of Persecution (Mid-Second to Early Fourth Centuries) -- Introduction: The Impact of Persecution -- Ch. 3. Greek Literature -- Ch. 4. Beginnings of Latin Literature -- Pt. 3. Literature of the Ascending Imperial Church (Early Fourth Century to ca. 430) -- Introduction: Essential Features of the History of the Fourth Century -- Ch. 5. First Phase of Arianism -- Ch. 6. Apollinarianism and the Second Phase of Arianism -- Ch. 7. Pastors, Exegetes, and Ascetics -- Ch. 8. Monastic and Hagiographic Literature -- Ch. 9. Augustine of Hippo -- Pt. 4. Literature of the Transition from Late Antiquity to the Early Middle Ages (ca. 430 to the Mid-Eighth Century) -- Introduction: Retrospective Collections and Progressive Works -- Ch. 10. Theological Controversies of the Fifth Century -- Ch. 11. Literature of the Latin West -- Ch. 12. Literature of the Greek East -- Pt. 5. Literature of the Christian East -- Ch. 13. Independent Bodies of Literature -- Supplementary Bibliography / William Harmless.
Includes bibliographical references (p. [581]-604) and indexes.
Keywords: Fathers of the church -- History and criticism; Church history -- Primitive and early church, ca. 30-600 -- Sources; Theology, Doctrinal -- History -- Early church, ca. 30-600.